EVALUATION OF CHONDROPROTECTIVE EFFICACY OF TRIAMCINOLONE IN OSTEOARTHRITIS INDUCED RAT MODEL - Noaman Ishaq; Quratulain Mehdi; Novera Sohail Bajwa; Shabana Ali; Bushra Shaheen; Muhammad Waqar Aslam Khan (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Osteoarthritis (OA) is one of the most common joint diseases afflicting human, characterized by progressive degeneration of articular cartilage in which chondrocytes fails to repair adequately. The objective of this study is to evaluate the chondroprotection treated by triamcinolone in osteoarthritis induced rat model.METHODOLOGY: This laboratory-based experimental study was conducted inthe Department of Pharmacology, Army Medical College, Rawalpindi, in collaboration with the National Institute of Health, Islamabad, from May-July2019.Osteoarthritis was induced by surgical removal of the medial meniscus and anterior cruciate ligament resection in the right knee joint of Sixteen (16) anesthetized rats of Sprague Dawley breed. They were divided into two (02) groups, with eight (08) rats in each group. Group-I was disease control in which 0.2 ml Intraarticular saline was administered for three weeks. While in group-II, a treatment group was treated with 70 µl intraarticular triamcinolone once weekly for three weeks. After that gait pattern of rats was scored. Animals were euthanized with overdosage of inhaled chloroform and a sample of proximal tibia was taken for histopathological analysis.RESULTS: The mean gait score of the control group and treatment group was 3.25±.707 and 2.25±.463 with a p-value of 0.006 that is statistically significant. While mean histopathological modified Mankin score of the control and treatment group was 11.5±1.195 and 8.5±1.195, respectively, with a significant p<0.001.CONCLUSION: Intraarticular administration of triamcinolone in osteoarthritis-induced rats resulted in improvement in gait pattern and histopathology.